Exploration of Species and Spatial Distribution Non-Timber Forest Products Using Geographic Information System (GIS) - Latifah, Siti; Agus Purwoko; Jeffry William Siregar (Journal of Sylva Indonesiana, 2023)
This study was conducted to look at the types and spatial distribution of non-timber forest products (NTFPs). Data on NTFPs species, distribution, and parts used was obtained through species identification. Meanwhile, NTFP mapping activities use GIS. The results showed that there were 8 types of NTFPs used by the villagers, namely Arenga pinnata, Hevea brasiliensis, Durio zibethinus, Areca catechu, Theobroma cacao, Parkia speciosa, Lansium parasiticum, and Archidendron pauciflorum. They use it for daily consumption and sell it to collectors in the form of fresh fruit, palm sugar, leaves, roots, seeds, and sap. Non-timber forest products are scattered in clusters and unevenly in the village area.